A histomorphometric study of unmyelinated fibers of the fibular nerve in Wistar rats - Tognon-Miguel, Vânia; Nascimento-Elias, Adriana Helena do; Schiavoni, Maria Cristina Lopes; Barreira, Amilton Antunes (Arquivos de Neuro-Psiquiatria, 2016)
There are few histomorphometric studies on the unmyelinated fibers of the fibular nerve in rats, and the number of experimental studies using this nerve has been increasing in the last years. Sixty-two percent of the endoneurial area from 10 fibular nerves of adult Wistar rats was scanned by electron microscopy, and digitized. The total number of unmyelinated axons (1.882 ± 271) was significantly lesser, and their axon diameters (0.2 μm to 2.8 μm) significantly higher than that determined in previous studies. The histogram peaked at 1 μm. The differences could be due to the nerve sampled area, the number and the age of the animals evaluated, and the laboratory techniques used. This study brings new and referential data to be used in experimental investigations involving histomorphometric evaluation of the rat fibular nerve.
Keywords: unmyelinated fibers, unmyelinated; peroneal nerve; microscopy, electron, transmission; peripheral nerves